Pengenalan Literasi Bahasa Inggris Siswa Tingkat Awal melalui Pembuatan Prakarya - Heriyanti Tahang; Risda Irianti; Elsiani Pokko; Filzah Maharani Salsabila; Rizky Ekawaty Ahmad (Abdimas: Papua Journal of Community Service, 2023)
English is a new thing for early-grade students at SD Negeri 29 Kota Sorong, even though the introduction of English can be done in various exciting ways, one of which is making crafts appropriate to the age of early-grade students. In this activity, the introduction to English is carried out by making crafts using attractive shapes and colors and by forming objects by sticking origami paper to shape houses or caterpillars using simple English. Partners participating in this activity were 30 students from grade 1 and 16 from grade 2 at SD Negeri 29 Kota Sorong. The results of this activity showed that the early grades were very enthusiastic about getting to know colors and shapes in English. They are very responsive, passionate, and active in demonstrating the work made.